(untitled) (Research, Society and Development, 2020)
Objective: The aim of this study was to evaluate the diagnostic capability of dentists in the identification of suggestive images of calcified carotid artery atheroma (CCAA) on panoramic radiographs (PRs) before and after using a problem-based learning method (PBL). Methodology: Five dentists (no specialists in oral and maxillofacial radiology) analyzed 102 digital PRs divided into: PRs with suggestive images of CCAA (n=51) and without suggestive images of CCAA (n=51). After the first analysis, the examiners attended an activity on soft tissue calcifications using the PBL method. Afterwards, they analyzed the 102 PRs again. The results of the analysis were calculated using the Cohen’s Kappa Test and the Receptor Operational Characteristic Curves (ROC). Results and Discussion: Regarding examiners’ performance before and after the activity, the intra-examiner test showed reasonable Kappa coefficients (0-0.40). For inter-examiner agreement after the activity, the Kappa coefficient was almost perfect (> 0.80). When comparing examiners’ performance after the activity with a template performed by an experienced radiologist, the Kappa Coefficient was > 0.80 with significant agreement (p<0.05). Conclusion: The precision and the probability of correctly detecting suggestive images of CCAA on PRs increased when the examiners participated in the active pedagogical method. The continuing education of the dentist and how it can make a difference in the systemic health of patients should be considered.